Iodine-catalyzed aromatization of tetrahydrocarbazoles and its utility in the synthesis of glycozoline and murrayafoline A: a combined experimental and computational investigation - Humne, Vivek T.; Dangat, Yuvraj B.; Vanka, Kumar; Lokhande, Pradeep (Organic & Biomolecular Chemistry, 2014)
A new protocol for the aromatization of tetrahydrocarbazoles has been achieved using a catalytic amount of iodine, giving high yields. The role of iodine in the aromatization has been explained by DFT, and its wide scope is extended to the total synthesis of glycozoline and murrayafoline A. This method has proven to be tolerant of a broad range of functional groups.

Intramolecular dehydrogenative coupling of 2,3-diaryl acrylic compounds: access to substituted phenanthrenes - Gupta, Vijay; Rao, V. U. Bhaskara; Das, Tamal; Vanka, Kumar; Singh, Ravi P. (Journal of Organic Chemistry, 2016)
A simple, facile, and environmentally benign intramolecular dehydrogenative coupling of various 1,2-diarylethylenes for the synthesis of phenanthrenes in excellent yield has been described. This new methodology uses ceric ammonium nitrate (CAN) as a promoter at room temperature and has been extended to intermolecular synthesis of biaryl compounds. The electron transfer from methoxyarene to cerium leads to cationic radical formation, which further proceeds to intramolecular coupling. Preliminary mechanistic investigation by EPR spectroscopy and density functional theory calculation suggested a similar view.

Interplaying anions in a supramolecular metallohydrogel to form metal organic frameworks - Karak, Suvendu; Kumar, Sushil; Bera, Saibal; Diaz Diaz, David; Banerjee, Subhrashis; Vanka, Kumar; Banerjee, Rahul (Chemical Communications, 2017)
The remarkable effect of anions on the transition from supramolecular gels to crystalline phases has been described. An amino acid-based metallohydrogel was transformed into different metal-organic frameworks through the selective picking of anions. The metallohydrogel and the resulting metal-organic frameworks (MOFs) were thoroughly characterized. The results demonstrated controlled access over the binding of a particular anion to selectively form a particular MOF.

Iron Catalyzed Hydroformylation of Alkenes under Mild Conditions: Evidence of an Fe(II) Catalyzed Process - Pandey, Swechchha; Raj, K. Vipin; Shinde, Dinesh R.; Vanka, Kumar; Kashyap, Varchaswal; Kurungot, Sreekumar; Vinod, C. P.; Chikkali, Samir H. (Journal of the American Chemical Society, 2018)
Earth abundant, first row transition metals offer a cheap and sustainable alternative to the rare and precious metals. However, utilization of first row metals in catalysis requires harsh reaction conditions, suffers from limited activity, and fails to tolerate functional groups. Reported here is a highly efficient iron catalyzed hydroformylation of alkenes under mild conditions. This protocol operates at 10-30 bar syngas pressure below 100 degrees C, utilizes readily available ligands, and applies to an array of olefins. Thus, the iron precursor [HFe(CO)(4)](-)[Ph3PNPPh3](+) (1) in the presence of triphenyl phosphine catalyzes the hydroformylation of 1-hexene (S2), 1-octene (S1), 1-decene (S3), 1-dodecene (S4), 1-octadecene (S5), trimethoxy(vinyl)silane (S6), trimethyl(vinyl)silane (S7), cardanol (S8), 2,3-dihydrofuran (S9), allyl malonic acid (S10), styrene (S11), 4-methylstyrene (S12), 4-iBu-styrene (S13), 4-tBu-styrene (S14), 4-methoxy styrene (S15), 4-acetoxy styrene (S16), 4-bromo styrene (S17), 4-chloro styrene (S18), 4-vinylbenzonitrile (S19), 4-vinylbenzoic acid (S20), and allyl benzene (S21) to corresponding aldehydes in good to excellent yields. Both electron donating and electron withdrawing substituents could be tolerated and excellent conversions were obtained for S11-S20. Remarkably, the addition of 1 mol % acetic acid promotes the reaction to completion within 16-24 h. Detailed mechanistic investigations revealed in situ formation of an iron-dihydride complex [H2Fe(CO)(2)(PPh3)(2)] (A) as an active catalytic species. This finding was further supported by cyclic voltammetry investigations and intermediacy of an Fe(0)-Fe(II) species was established. Combined experimental and computational investigations support the existence of an iron-dihydride as the catalyst resting state, which then follows a Fe(II) based catalytic cycle to produce aldehyde.

Insights into the origin of life: did it begin from HCN and H2O? - Das, Tamal; Ghule, Siddharth; Vanka, Kumar (Acs Central Science, 2019)
The seminal Urey-Miller experiments showed that molecules crucial to life such as HCN could have formed in the reducing atmosphere of the Hadean Earth and then dissolved in the oceans. Subsequent proponents of the "RNA World" hypothesis have shown aqueous HCN to be the starting point for the formation of the precursors of RNA and proteins. However, the conditions of early Earth suggest that aqueous HCN would have had to react under a significant number of constraints. Therefore, given the limiting conditions, could RNA and protein precursors still have formed from aqueous HCN? If so, what mechanistic routes would have been followed? The current computational study, with the aid of the ab initio nanoreactor (AINR), a powerful new tool in computational chemistry, addresses these crucial questions. Gratifyingly, not only do the results from the AINR approach show that aqueous HCN could indeed have been the source of RNA and protein precursors, but they also indicate that just the interaction of HCN with water would have sufficed to begin a series of reactions leading to the precursors. The current work therefore provides important missing links in the story of prebiotic chemistry and charts the road from aqueous HCN to the precursors of RNA and proteins.

Insights into chemical reactions at the beginning of the universe: from HeH+ to H-3 (+) - Dash, Soumya Ranjan; Das, Tamal; Vanka, Kumar (Frontiers in Chemistry, 2021)
At the dawn of the Universe, the ions of the light elements produced in the Big Bang nucleosynthesis recombined with each other. In our present study, we have tried to mimic the conditions in the early Universe to show how the recombination process would have led to the formation of the first ever formed diatomic species of the Universe: HeH+, as well as the subsequent processes that would have led to the formation of the simplest triatomic species: H-3 (+). We have also studied some special cases: higher positive charge with fewer number of hydrogen atoms in a dense atmosphere, and the formation of unusual and interesting linear, dicationic He chains beginning from light elements He and H in a positively charged atmosphere. For all the simulations, the ab initio nanoreactor (AINR) dynamics method has been employed.
Keywords: ab initio molecular dynamics; ab initio nanoreactor; Density functional theory; origin of molecules in the universe; the earliest lewis acid

Insights into the nature of self-extinguishing external donors for ziegler-natta catalysis: a combined experimental and DFT study - Vipin Raj, K.; Kumawat, Jugal; Dhamaniya, Sunil; Subaramanian, Murugan; Balaraman, Ekambaram; Kumar Gupta, Virendra; Vanka, Kumar; Grubbs, Robert H. (ChemCatChem, 2021)
Developing donors for Ziegler-Natta (ZN) catalysis to control the polymerization reaction and produce polymers with desirable properties has always been challenging due to the multi-component nature of the catalytic systems. Here, we have developed a new synthetic protocol for making two external donors, D-1 (2,2,2-trifluoroethyl myristate) and D-2 (2,2,2-trifluoroethyl palmitate) that show self-extinguishing properties, followed by a systematic DFT study to understand this peculiar property of these donors. D-1 and D-2 can undergo parallel reactions with aluminum and titanium species present in the system to produce ketones and aldehydes, which are poisons for ZN catalytic systems, thus explaining their self-extinguishing nature. The non-covalent interaction between the long alkyl chain of the donors with the surface plays a vital role in determining the donors ` self-extinguishing nature. There is a significant thermodynamic preference for the binding of the donor with the longer alkyl chain at the titanium center. The current work, therefore, provides interesting insights into how self-extinguishing donors function in ZN catalytic systems.
Keywords: DFT; donors; non-covalent interactions; self-extinguishing; Ziegler-Natta catalysis

In silico discovery of a neutral 2π aromatic silicon aluminum compound - Sharma, Himanshu; Vanka, Kumar (Organometallics, 2024)
The recently developed ab initio nanoreactor (AINR) approach to identifying reaction intermediates and pathways without the necessity of experimental input has been employed in the current work to locate new cyclic silicon-based structures that have the potential to display aromaticity. Using this approach, we have identified many cyclic silicon-based molecules that have been experimentally reported over the past three decades. More importantly, the current work showcases an interesting new molecule that has been discovered through this approach: a four-membered cyclic compound of silicon and aluminum that displays significant 2 pi aromaticity and is capable of the activation of important small molecules such as ammonia.

Iron-catalyzed (E)-selective hydrosilylation of alkynes: scope and mechanistic insights - Sen, Anirban; Tewari, Tanuja; Kumar, Rohit; Vinod, C. P.; Sharma, Himanshu; Vanka, Kumar; Chikkali, Samir H. (Catalysis Science and Technology, 2024)
Iron-catalyzed hydrosilylation of internal alkynes has been rarely reported. Even in these rare cases, additives have been used for the success of the reaction, which often creates a problem for the functional group tolerance of the reaction. Herein, we report an additive-free iron-catalyzed (E)-selective hydrosilylation of internal alkynes in the presence of a phosphine ligand. A low-valent Fe(0) complex [Fe(CO)(3)(BDA)] {[Fe-1]} catalyzed the hydrosilylation of alkynes at 60 to 120 degrees C, exhibited a broad substrate (24 substrates) scope and tolerated different functional groups. The synthetic utility of the reaction was demonstrated by a gram scale experiment, preparing alkenes, and by chemo-selective hydrosilylation. The modus operandi of the reaction has been investigated by i) homogeneity test, ii) radical trapping experiments, iii) X-ray photoelectron spectroscopy, and iv) by preparing a Fe(II) complex as catalyst control. These mechanistic investigations revealed a two-electron pathway for the hydrosilylation of alkynes. In addition, kinetic investigations were undertaken to shed light on the rates of the reaction. Kinetic studies suggest the absence of an induction period, and the reaction is first order with respect to the concentration of iron catalyst [Fe-1] and zeroth order with respect to the substrate (alkyne). The Hammett plot suggests that strongly electron-withdrawing groups on the alkyne favour the hydrosilylation reaction. Meanwhile Eyring analysis suggests that the rate-determining step likely involves an associative pathway. Based on the findings of the mechanistic and kinetic investigation, a plausible Chalk-Harrod-type mechanism is likely to be operative. The proposed mechanism is substantiated by computational investigations, which suggested that the Chalk-Harrod mechanism is kinetically more favored by 15.8 kcal mol(-1) over the modified Chalk-Harrod mechanism.

Investigating the visible range photoresponse of an organic single-crystal analogue of the green fluorescent protein - Virole, Vishal; Dabke, Niteen; Verma, Sahil; Kumar, Ajay; Pandya, Rinu; Husale, Sudhir; Vanka, Kumar; Gonnade, Rajesh; Kanawade, Rajesh (Nanoscale, 2025)
The growing demand for lightweight, flexible, semi-transparent and low-cost photodetectors (PDs) in wearable electronics and optical communication systems has prompted studies to investigate organic materials as feasible alternatives to conventional inorganic PDs. However, modern organic PDs often face responsivity, detectivity, and photoresponse speed limitations, particularly in the visible range. Here, we present the photoresponse of an organic single-crystal analogue of the green fluorescent protein (GFP) chromophore photodetector, fabricated on a silicon nitride substrate. A significant increase in photocurrent was detected upon illumination with visible wavelengths (532 nm, 630 nm, and halogen light). A remarkably consistent and repeatable photoresponse was obtained during the ON and OFF illumination cycles. The device showed the dependence of photocurrent on the applied bias voltages. The measured photocurrent, responsivity, detectivity, rise time, decay time, noise equivalent power and external quantum efficiency are studied for different wavelengths. Strikingly, the fabricated device demonstrates excellent performance in the visible region compared to several conventional organic and inorganic PDs. The observed responsivity and detectivity values for the device are 98 mA W-1 and 7.94 x 108 Jones, respectively. Furthermore, the device also exhibits rapid photoresponse dynamics with a rise time of 180 ms and a decay time of 152 ms. The excellent photodetection features indicate that the single crystal GFP could serve as a versatile broadband material for future applications in optoelectronics.

Iron-catalyzed chemoselective reduction of enimines to N-Allylic amines via hydrosilylation - Tewari, Tanuja; Shaikh, Maulali H.; Sharma, Himanshu; Vanka, Kumar; Chikkali, Samir H. (Asian Journal of Organic Chemistry, 2025)
Chemoselective hydrosilylation of unsaturated imines is challenging as the two double bonds compete for the reaction. Here in, we report an iron-catalyzed chemoselective hydrosilylation of enimines leading to the generation of allyl amines in the presence of phosphine ligand. A low-valent Fe(0) complex [(BDA)Fe(CO)3] catalyzed the hydrosilylation of enimine at room temperature and exhibited broad substrate scope including a variety of enimine (cinnamylimine, allylimine) and ketimine. Mechanistic investigations revealed that the reaction proceeds through an oxidative addition of the silane compound, leading to the formation of an iron hydride intermediate. Subsequently, a two-electron pathway facilitates the hydrosilylation of the enimine substrate. This has been supported by preparing a well-defined Fe(II)-silane complex and using it as a catalyst control. Based on experimental and computational investigations, a plausible Chalk-Harrod-type mechanism is proposed.
Keywords: Cinnamyl amine; Imine hydrosilylation; iron catalysis; Iron hydride; Phosphine